MONETARY ECONOMY OF CENTRAL ASIA DURING THE REIGN OF THE SHEIBANID DYNASTY - Пустовая Елена Сергеевна (Bright Mind Publishing, 2025)
The article is devoted to the analysis of the monetary economy of Central Asia during the reign of the Shaybanid dynasty. The author examines the development of the monetary system, including the issue of copper and silver coins, monetary reforms and the policy of minting in Bukhara, Samarkand, Hisar and other regions. Special attention is paid to the impact of political events, civil strife and reforms on inflation, the weight of coins and their circulation. analyzes the reform of Abdullah Khan II and its importance for the stabilization of money circulation.